Biocompatibility of a Ti-Rich Medium-Entropy Alloy with Glioblastoma Astrocytoma Cells - Ho, Wen-Fu; Wong, Ka-Kin; Lee, Mei-Hwa; Thomas, James L.; Chang, Ya-Chun; Wu, Shih-Ching; Hsu, Hsueh-Chuan; Lin, Hung-Yin (International journal of molecular sciences, 2022)
Titanium and titanium alloys are widely used in medical devices and implants; thus, the biocompatibility of these metals is of great importance. In this study, glioblastoma astrocytoma cellular responses to Ti65-Zr18-Nb16-Mo1 (Ti65M, metastable medium-entropy alloy), Ti-13Nb-7Sn-4Mo (TNSM, titanium alloy), and commercially pure titanium (CP-Ti) were studied. Several physical parameters (crystal phase structure, surface roughness and hardness) of the titanium alloys were measured, and the correlation with the cellular viability was investigated. Finally, the relative protein expression in cellular proliferation pathways was measured and compared with mRNA expression assessed with quantitative real-time reverse transcription polymerase chain reaction assay (qRT-PCR).